Cognitive Empathy and Solidarity in Children’s Literature: Nikolajeva’s Reading of the KKPPK Series "Sampahku, Sahabatku" - Rahmawati, Anisa Asih; Indriyani, Jiphie Gilia (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The shift in social values from collectivism toward individualism poses a significant challenge to child development in the digital era. This study aims to identify the various forms of solidarity values within the Kecil-Kecil Punya Karya (KKPK) book series titled Sampahku Sahabatku (both novel and comic versions) and to analyze the textual mechanisms employed to construct reader empathy through Maria Nikolajeva’s cognitive theory. Utilizing a descriptive qualitative method, this research examines how narration and characterization facilitate cognitive identification in children aged 6–12. The findings indicate that solidarity values in the text are manifested into four primary categories: mutual trust, social responsibility, interpersonal care, and the culture of mutual cooperation (gotong royong). Through Nikolajeva’s perspective, it is revealed that the "by children, for children" narrative approach effectively stimulates the readers’ mental functions to profoundly comprehend social consequences and character emotions. These findings underscore that children’s literature serves a strategic function as a medium for revitalizing human values and acts as a balancing instrument against the social isolation caused by technological advancements. Theoretically, this article enriches the study of children’s literature by integrating social value analysis with cognitive narrative development.